Mind Mapping: Reading Comprehension Technique of Arabic Texts for Students in Higher Education - Muassomah, Muassomah; Yurisa, Penny Respaty; bin Yahaya, Mohd Firdaus (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
In the context of the curriculum in Madrasah (Islamic school), using mind mapping in the learning process of Arabic text reading skills is an alternative chosen to improve student's reading competence. This study aimed to describe the design process of learning Arabic text reading skills by utilizing mind mapping techniques, as well as showing the form of mind mapping that has been prepared by students individually and in groups. Qualitative method was a suitable method used in this research with the object of research was students of Arabic language study program. The research data was extracted through observation and documentation. Observation is done by observing the course of the learning process and documentation in the form of student work in the form of mind mapping is analyzed. The International Class Program (ICP) of students selected in this study amounted to 50 students in department of Arabic Language and Literature at Universitas Islam Negeri Maulana Malik Ibrahim, Malang.The findings of this study showed that the compiled mind mapping shows the creativity of students, where each student makes a different and varied mind map, both in shapes, colors, and hyphens. The concept of the Buzan model mind mapping used in this study. This study concluded that learning text reading skills using mind mapping has made students more creative, active, confident, and easy to understand.